2016
DOI: 10.1038/cddis.2016.370
|View full text |Cite
|
Sign up to set email alerts
|

ERK/Drp1-dependent mitochondrial fission is involved in the MSC-induced drug resistance of T-cell acute lymphoblastic leukemia cells

Abstract: The bone marrow microenvironment facilitates the proliferation and survival of leukemia cells, contributing to disease relapse. Bone marrow-derived mesenchymal stem cells (MSCs) are well known to promote cancer chemoresistance via soluble factors and cell adhesion. However, little is known about the effects of MSCs on the mitochondrial dynamics of T-cell acute lymphoblastic leukemia (T-ALL) cells, or how this may influence the chemoresistance of these cells. Here, we tested both indirect (Transwell) and direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 50 publications
(46 reference statements)
4
68
0
Order By: Relevance
“…Our results showed that miR-488 induced mitochondrial fusion, with downregulation of p-Drp1 and Fis1. Drp1 phosphorylation and Fis1 upregulation promotes their mitochondrial membrane localization and induces mitochondrial fission [ 28 ], which was in accord with fragmented mitochondrial shape. Drp1-dependent mitochondrial dynamics may confer either apoptosis or resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that miR-488 induced mitochondrial fusion, with downregulation of p-Drp1 and Fis1. Drp1 phosphorylation and Fis1 upregulation promotes their mitochondrial membrane localization and induces mitochondrial fission [ 28 ], which was in accord with fragmented mitochondrial shape. Drp1-dependent mitochondrial dynamics may confer either apoptosis or resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Six1 has been reported to activate ERK signaling in several cancers [ 38 , 39 ]. It has been reported that activation of ERK signaling could lead to Drp-1 phosphorylation and mitochondrial fission, which is involved in the drug resistance of leukemia cells [ 28 ]. Thus Six1 may induce mitochondrial fission through ERK/Drp1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Drp1 is a GTPase that regulates mitochondrial fission. Leukemia cells overexpressing wild-type Drp1 or Drp1 S616E presented fragmented mitochondria, reduced mitochondrial ROS levels, increased glycolysis, and improved drug resistance (299)(300)(301). Drp1 S616 phosphorylation through the stimulation of mitochondria fission and glycolysis seemed required to RAS-induced transformation (302).…”
Section: Targeting Mitochondria Metabolismmentioning
confidence: 98%
“…Reportedly, src-mediated phosphorylation of Caveolin-1 at Y14 was essential for EGFR activation or its interaction with β1 integrin promoted Fyn-dependent Src homology and Erk1/2 phosphorylation, which was closely linked to chemoresistance [ 32 ]. Cai et al [ 33 ] found that Erk-mediated phosphorylation of Drp1 at residue S616 contributed to the mitochondrial fusion, a low mitochondrial ROS level, a high proglycolytic shift and drug resistance of T-cell acute lymphoblastic leukemia cells, treated with mesenchymal stem cells. Dong et al [ 34 ] found that Derlin-1 overexpression mediated chemoresistance of bladder cancer through PI3K/Akt and Erk/MMP signaling.…”
Section: Introductionmentioning
confidence: 99%